Message Authentication Using New Hash Function - Abdulah, Hasanen S; Al-Rawi, Maha A Hamood; Hammod, Dalal N (Al-Nahrain Journal of Science, 2018)
In cryptography, hash functions have very important effects when it’s used in the message integrity, digital time stamping, and digital signature. Hash functions compute hash value by a set of logical (primitive) operations that perform on a (32) bit words for authentication. Authentication process becomes very important especially manipulated message undetected that can have disastrous effects in Network Management and E-Commerce. In this paper, a proposal for new hash function based on MD5 is developed. The length of message digest is 224-bit through (4) rounds that each round has a pair of (16) steps. The final number of steps is (128) that make stronger function against collision attests and more secure than MD5.